The Influence of Principal’s Competence and Mastery of Information Technology on the Performance of Islamic Education Teachers - Indra Devi; Iswantir Iswantir; A’rafky John (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: The Influence of Principal’s Competence and Mastery of Information Technology on Teacher PerformanceObjective: This study investigates the influence of principal competence and mastery of information technology (IT) impact teacher performance at SMP Negeri 1 Tigo Nagari, Pasaman Regency, in 2024. Methods: This study uses a quantitative correlational approach. The sample of this study amounted to 46 Islamic education teachers. Data collection: Questionnaires were used to collect data. Data analysis: Data were analyzed using the classical assumption test, including test for normality, multicollinearity, heteroscedasticity, followed by multiple linear regression analysis, F test, and coefficient of determination test. Results and conclusions: The ANOVA results indicated a significant regression model (F = 17.637, p = 0.000). The findings demonstrate that both principal competence and IT mastery have a positive and significant effect on teacher performance at SMPN 1 Tigo Nagari. Contribution: This study contributes as a guide for principals in improving their competence to create a productive work environment and support the improvement of teacher performance.INDONESIAN: Pengaruh Kompetensi Kepala Sekolah dan Penguasaan Teknologi Informasi terhadap Kinerja Guru Pendidikan Agama IslamTujuan: Studi ini bertujuan untuk menentukan bagaimana Kompetensi kepala sekolah dan penguasaan TI berdampak pada kinerja guru di SMP Negeri 1 Tigo Nagari Kab. Pasaman tahun 2024. Metode: Penelitian ini menggunakan pendekatan kuantitatif korelasi. Sampel penelitian ini berjumlah 46 orang guru. Pengumpulan data: Angket digunakan dalam proses mengumpulkan data. Analsisi data: data dianalisis menggunakan uji asumsi klasik berupa uji normalitas, uji multikolinearitas, uji heteroskedastisitas, dan analisis regresi linier berganda, uji F, dan Uji Determinasi. Hasil dan kesimpulan: Hasil ANOVA menunjukkan model regresi signifikan (F = 17,637, p = 0,000). Hasil analisis menyimpulkan bahwa kompetensi kepala sekolah (dan penguasaan teknologi informasi berpengaruh positif dan signifikan terhadap kinerja guru di SMPN 1 Tigo Nagari. Kontribusi: Penelitian ini berkontribusi sebagai panduan bagi kepala sekolah dalam meningkatkan kompetensinya untuk menciptakan lingkungan kerja yang produktif dan mendukung peningkatan kinerja guru.